Sosialisasi Dampak Penggunaan Smartphone terhadap Disiplin Waktu Belajar Anak di Desa Mendalo Darat - Adang Ridwan; Ria Karmila (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The purpose of this service is to reveal the socialization of the impact of smartphone use in managing (managing) study time. This research method uses a qualitative descriptive method, the implementation is carried out with observation, providing socialization, the first activity is showing videos, the second activity is providing material in power point, the impact of smartphone use. The results of this study indicate that the socialization of the positive impact of smartphone use has provided knowledge for students that wrong smartphone users can have a negative impact on child development, but if the use of smartphones is in accordance with learning needs and is supervised in its use, it will have a good impact on children. These children are very important considering that there are still many people, especially housewives, who do not realize the lack of control over excessive smartphone use by children is very dangerous and dangerous to use.